Comprehensive Molecular Profiling for Relapsed/Refractory Pediatric Burkitt Lymphomas—Retrospective Analysis of Three Real-Life Clinical Cases—Addressing Issues on Randomization and Customization at the Bedside - Polaskova, Kristyna; Merta, Tomas; Martincekova, Alexandra; Zapletalova, Danica; Kyr, Michal; Mazanek, Pavel; Krenova, Zdenka; Mudry, Peter; Jezova, Marta; Tuma, Jiri; Skotakova, Jarmila; Cervinkova, Ivana; et al. (Frontiers in Oncology, 2020)
In order to identify reasons for treatment failures when using targeted therapies, we have analyzed comprehensive molecular profiles of three relapsed, poor-prognosis Burkitt lymphoma cases. All 3 cases had resembling clinical presentation and histology and all three patients relapsed, but their outcomes differed significantly. The samples of their tumor tissue were analyzed using whole exome sequencing, gene expression profiling, phospho-proteomic assays and single cell phospho-flow cytometry. These results explain different treatment responses of the three histologically identical but molecularly different tumors. Our findings support personalized approach for patient with high risk, refractory and rare diseases and may contribute to personalized and customized treatment efforts for patients with limited treatment options like relapsed/refractory Burkitt lymphoma.